Memórias da gastronomia a partir das cozinhas hoteleiras em Foz do Iguaçu - Martins, Lavínia Raquel Martins de (2023)
This doctoral investigation is based on exploring the relationship between gastronomy, memory and hospitality in the hotel kitchens of Foz do Iguaçu. The city is a tourist attraction, however, little is known about the contribution of local hotel kitchens to the hospitality experience of visitors. The research is developed by observing the history of culinary professionals in the hotel industry, a social organization that has been little researched in a scientific way. The overall aim of this thesis is to investigate the gastronomy of hotel establishments, through the memories of cooks, as a form of hospitality in Foz do Iguaçu in the period 1970/80/90. Describing hotel hospitality as a means of enabling the perception of established social relationships; historicizing gastronomy, in the hotel industry of Foz do Iguaçu, contextualizing how hospitality occurs in the region and; presenting the gastronomic representation in the hotel industry of Foz do Iguaçu through the memories of the cooks of the city's hotel establishments. For this purpose, the methodology is described, grounded in historical research, with the intention of understanding the social relations of hospitality in Foz do Iguaçu's hotel society through an analysis of the memories of professional cooks. The focus goes back to the 1970s/80s/90s. The research is exploratory and takes place through interviews with hotel cooks, which become our channel to capture memories intertwined with the social and cultural history of Foz do Iguaçu. The history of gastronomy in hospitality spans centuries and civilizations, emphasizing food as a social and cultural link. The development of eating practices over time reflects societies. In Foz do Iguaçu, over the decades, hospitality has stood out for its diversity of entertainment, including tourism agencies and outdoor activities. The local gastronomy was linked to subsistence, trade, and hunting and fishing practices, reflecting the community's involvement in food production for visitors. The findings in this research offer insight into the way in which gastronomy and hospitality have intertwined and, over the decades, shaped the society of Foz do Iguaçu. The research contributed to the gastronomic representation of the hotel industry in Foz do Iguaçu, by exploring the memories of the cooks who worked in the city's hotel establishments, a pattern was identified in which the municipality stood out as a consumer of the region's fish, a characteristic that is reflected in the offer of this food in all the hotels mentioned during the interviews. It is evident that, with the accounts of gastronomic hospitality offered in Foz do Iguaçu's hotel industry, its representation is linked to the border countries (Argentina and Paraguay) as well as to the cultures of the immigrants and migrants who live here. Characterizing itself as a city of cultural and gastronomic diversity. This study revealed the value of memories of gastronomy and of hotel cooks as connoisseurs of the cuisines used in this city and stories of the gastronomic culture of Foz do Iguaçu. As we continue to explore these memories, we enhance the culinary diversity and hospitable cultural heritage this region has to offer.